Evodiamine, a Novel NOTCH3 Methylation Stimulator, Significantly Suppresses Lung Carcinogenesis in Vitro and in Vivo - Su, Tao; Yang, Xia; Deng, Jian-Hua; Huang, Qiu-Ju; Huang, Su-Chao; Zhang, Yan-Min; Zheng, Hong-Ming; Wang, Ying; Lu, Lin-Lin; Liu, Zhong-Qiu (Frontiers in Pharmacology, 2018)
Lung cancer is a leading cause of cancer-related deaths worldwide. NOTCH3 signaling is mainly expressed in non-small cell lung carcinoma (NSCLC), and has been proposed as a therapeutic target of NSCLC. While, few agents for preventing or treating NSCLC via targeting NOTCH3 signaling are used in modern clinical practice. Evodiamine (EVO), an alkaloid derived from Euodiae Fructus, possesses low toxicity and has long been shown to exert anti-lung cancer activity. However, the underlying anti-lung cancer mechanisms of EVO are not yet fully understood. In this study, we explored the involvement of NOTCH3 signaling in the anti-lung cancer effects of EVO. Urethane-induced lung cancer mouse model and two NSCLC cell models, A549 and H1299, were used to evaluate the in vivo and in vitro anti-lung cancer action of EVO. A DNA methyltransferases inhibitor was employed to investigate the role of NOTCH3 signaling in the anti-lung cancer effects of EVO. Results showed that EVO potently reduced tumor size and tumor numbers in mice, and inhibited NOTCH3 in the tumors. EVO also dramatically reduced cell viability, induced G2/M cell cycle arrest, inhibited cell migration and reduced stemness in cultured NSCLC cells. Mechanistic studies showed that EVO potently inhibited NOTCH3 signaling by activation of DNMTs-induced NOTCH3 methylation. Importantly, inhibition of NOTCH3 methylation in NSCLC cells diminished EVO's anti-NSCLC effects. Collectively, EVO, a novel NOTCH3 methylation stimulator, exerted potent anti-lung cancer effects partially by inhibiting NOTCH3 signaling. These findings provide new insight into the EVO's anti-NSCLC action, and suggest a potential role of EVO in lung cancer prevention and treatment.